2012
DOI: 10.1159/000337665
|View full text |Cite
|
Sign up to set email alerts
|

Orthodontic Treatment in the Management of Cleft Lip and Palate

Abstract: The orthodontic treatment of patients with all types of cleft lip and palate, a resume of facial growth and discussion on dental and occlusal development is presented. A fully integrated cleft team provides life-long interdisciplinary holistic treatment for patients born with an orofacial cleft. To understand the team approach to cleft care, this article should be read in close conjunction with those on speech therapy, surgery and alveolar bone grafting to determine the synergy required between these and other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…[17] In our patient, maxillary arch was not constricted and archwires were enough to correct the maxillary arch form.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…[17] In our patient, maxillary arch was not constricted and archwires were enough to correct the maxillary arch form.…”
Section: Discussionmentioning
confidence: 93%
“…[1213141516] In addition to ABG, orthodontic treatment represents another key factor for the success of the overall treatment of cleft patients, which usually includes expansion, comprehensive fixed orthodontic treatment, face mask therapy and possible pre-surgical orthodontics in cases requiring orthognathic surgery. [1718]…”
Section: Introductionmentioning
confidence: 99%
“…However, overall, the male gender is more affected by labio-palatine clefts than the female gender. It is generally accepted that there is a genetic component in the cause of clefts, about 40% of cases presenting a family history of labio-palatine cleft; this genetic predisposition is exacerbated by environmental factors [4].…”
Section: Abstract: Labi-palatine Clefts Medical Recovery Complex Tmentioning
confidence: 99%
“…Orthodontic treatment after growth completion. 19,20 In the world literature exists many controversies s about surgical timing and techniques of post-orthodontic procedures in the management and treatment of cleft lip and/or palate, therefore the aim of this review is to create summary and comparisons of the combination of different Orthodontic treatment protocols and different Surgery techniques performed in the management of patients born with cleft lip and/or palate.…”
Section: Introductionmentioning
confidence: 99%
“…25 Jorg A Lisson et al, 6 reported that the inhibition of maxillary growth in growing patient having complete bilateral and unilateral cleft lip, alveolus and palate occur after completion of primary surgery so it is necessary to consider surgical maxillary advancement after completion of a growth spurt in both types of clefts (Table 1). 6 Many authors recommended that full fixed orthodontic appliances should be conducted after maxillary expansion which is generally performed at age of 10 years and 7 months and Presurgical maxillary expansion is generally performed after secondary alveolar bone graft 20,26 but if cleft children had mid face deficiency or negative overjet (class III mal occlusion) the protraction of the maxillary segment by using face mask or head gear, mini implants (mini screws) or mini plates which provide an orthodontic force that can be used to correct maxillary segment to be in proper position is indicated and in order to provide better conditions for future bone grafting the maxillary expansion should be conducted at age of 9years 11 months, class III elastics may be used to correct the overjet. 19,26 In case of a severe maxillary reduction in Dorota et al recommended the use of thick-wire appliances such as expander and combination of a Delaire or Petite type face mask to reduce sagittal displacement of maxilla.…”
Section: Introductionmentioning
confidence: 99%